2014
DOI: 10.11138/mltj/2014.4.1.029
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings during and after Platelet Rich Plasma injections in tendons

Abstract: Platelet rich plasma has been used in the treatment of tendinopathies, but the sonographic modifications of tendons have received less attention. In this paper we report the results of an ultrasound evaluation, performed during and after plasma injection, in patients with tendinopathy. The sonographic abnormalities and neovascularization were registered in twenty tendons. Three plasma injections (once a week) were performed, and a rehabilitation program was recommended. Pain and patients' satisfaction were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…40 This increased the stiffness of the tendons and, combined with micro-ruptures of the fibers, probably decreased their ability to absorb the exercise loads in the course, and thus increased the risk of those soldiers being injured. [40][41][42] The increased prevalence of echo-type III and IV fibers in the currently injured group might also indicate that the compromised tendon structure is associated with compromised muscle activity around the joint. 43,44 Changed muscle activation may lead to a diminished capacity of the surrounding muscles to stabilize the joint, along with reduced maximal muscle force and altered neuromuscular control, which potentially predisposes the participants to musculoskeletal injury.…”
Section: Discussionmentioning
confidence: 99%
“…40 This increased the stiffness of the tendons and, combined with micro-ruptures of the fibers, probably decreased their ability to absorb the exercise loads in the course, and thus increased the risk of those soldiers being injured. [40][41][42] The increased prevalence of echo-type III and IV fibers in the currently injured group might also indicate that the compromised tendon structure is associated with compromised muscle activity around the joint. 43,44 Changed muscle activation may lead to a diminished capacity of the surrounding muscles to stabilize the joint, along with reduced maximal muscle force and altered neuromuscular control, which potentially predisposes the participants to musculoskeletal injury.…”
Section: Discussionmentioning
confidence: 99%
“…In a letter to the editor by Knobloch, et al (Knobloch et al 2008 ) in response to a published study of intratendinous injections for Achilles tendinopathy (Maxwell et al 2007 ), the authors raised concerns regarding the unknown effect of intratendinous level of collagen distribution on the potential adverse effects of intratendinous injections. Our study specifically examined the biomechanical effects, but other deleterious effects on tendon beyond physical disruption and biomechanical detrimental effects are also hypothesized (Abate et al 2014 ). Such proposed effects include risk of pressure-induced tissue necrosis and focal infections, as well as focal tendon hypoxia and elevated lactate concentrations in tendons with tendinosis (Knobloch et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results have shown only little or no structural improvement at short-to-midterm (6-14 months) follow-up while the data on tendon vascularity changes are conflicting. [4][5][6] Furthermore, these variables demonstrated poor correlation with clinical outcome. In a two-year prospective study evaluating the diagnostic and prognostic value of US and magnetic resonance (MR) imaging in the assessment of Achilles tendon disorders, Khan et al 7 reported that conventional US is not useful in monitoring Achilles tendon healing as US abnormalities persist even after patients have made good functional recovery.…”
Section: Introductionmentioning
confidence: 99%